Microplastics and sorbed contaminants - trophic exposure in fish sensitive early life stages - Cousin, Xavier; Batel, Annika; Bringer, Arno; Hess, Sebastian; Bégout, Marie-Laure; Braunbeck, Thomas (Marine environmental research, 2020)
The present study evaluated very small microplastic particle (MPs) transfer to zebrafish and marine medaka larvae via prey experimentally exposed to MPs from the onset of feeding. Larvae were fed Paramecium or Artemia nauplii loaded with fluorescent 1-5 or 10-20 μm MP. Pollutant accumulation was analyzed by optically tracking of benzo[a]pyrene (BaP) and recording cyp1a transcription. Paramecium transferred 1-5 μm particles only, whereas Artemia efficiently transferred both MPs. Although zebrafish and medaka larvae fed from the onset of active food intake (2-3 dph, respectively) on Paramecium and from days 6-7 post-hatch on Artemia nauplii, neither MP accumulation nor translocation to tissues was detected. MP egestion started within few hours after ingestion. Cyp1a induction and fluorescent analyses proved BaP bioavailability after transfer via Paramecium and Artemia. Unicellular or plankton organisms ingest contaminants via MPS and transfer effectively these to sensitive early life-stages of vertebrates, giving rise to whole-life exposure.
Gesehen am 03.12.2020